Utilization focused evaluation the new century text - Patton, Michael Quinn 1945- (Sage, 1997)
"Can evaluation be used to improve programs? Can it contribute to program effectiveness? Do evaluators bear any responsibility for evaluation use and program improvement? This skillfully honed revision by master storyteller and evaluator, Michael Quinn Patton, answers these questions and provides the most comprehensive review and integration ever done of the vast literature on evaluation use and practice. Entirely rewritten, this edition offers readers a full-fledged evaluation text from identifying primary users of an evaluation to focusing the evaluation, making methods decisions, analyzing data, and presenting findings." "Both practical and theoretical, Utilization-Focused Evaluation: The New Century Text, Third Edition tells how to conduct program evaluations and why to conduct them in the manner prescribed. Each chapter contains a review of the relevant literature and actual case examples to illustrate major points."--BOOK JACKET.